Generation Y and Digital Transformation: Determinants of Intention to Adopt E-Payment - Heri Faisal Harahap; Mutia Fitri Chania (Journal Of Management Analytical and Solution (JoMAS), 2025)
This study examines the factors influencing Generation Y’s intention to adopt ePayment services, using the Technology Acceptance Model (TAM) framework.The study involved 200 Generation Y respondents. The variables tested includeperceived usefulness, perceived ease of use, perceived risk, and subjectivenorms. Structural Equation Modeling-Partial Least Square (SEM-PLS) analysisrevealed that all variables significantly influence the intention to adopt ePayment. The findings indicate that perceived usefulness and ease of use havethe most substantial impact, reflecting the importance of efficient and accessiblesystems for users. Conversely, perceived risk, particularly concerning securityand privacy, acts as a primary barrier, highlighting the need for more securesystem development. Subjective norms also influence user intentions throughsocial pressures from family, friends, and other significant figures. This studyunderscores the importance of addressing perceived risks, enhancing systemusability, and leveraging social influence to promote e-Payment adoption amongGeneration Y. The findings offer strategic insights for technology developers,policymakers, and marketers to optimise e-Payment implementation and userengagement.